Traditional Public Transportation Service Levels of Middle City: A Systematic Literature Review : Tingkat Pelayanan Transportasi Umum Tradisional di Kota Menengah: Tinjauan Literatur Sistematis - Widyatni, Dini; Anugraha, Pebri Tri; Fadillah, Zahran Ditra; Juliar, Eka; Taufik, Mohammad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Middle Citys play a crucial role in the socio-economic landscape of developing cities, yet their integration with efficient public transportation systems remains a persistent urban challenge. This study presents a systematic literature review of research published between 2020 and 2025, aiming to evaluate the service levels of public transportation in Middle City environments. Using Publish or Perish and VOSviewer, 120 relevant studies were identified and analyzed across five key service dimensions: frequency, affordability, accessibility, safety, and user satisfaction. The findings reveal that while public transportation around Middle Citys is generally available, significant gaps remain in terms of affordability, safety, and inclusive access for vulnerable groups such as elderly users and informal workers. Geographic analysis shows that most research originates from rapidly urbanizing countries in Asia and Africa, highlighting regional concerns with informal commercial zones. This review underscores the urgent need for context-sensitive, participatory, and equity-focused planning approaches to improve public transport service quality in Middle Citys and similar urban environments..